THE IMPACT ON INFANT WEIGHT OF USING THE BABY-LED WEANING METHOD TO INTRODUCE COMPLEMENTARY FOODS - Ai Nur Zannah; Alfi Fahrani; Sugijati Sugijati; Kiswati Kiswati (Jurnal Kesehatan Kusuma Husada, 2025)
Background: During early childhood, a period of rapid growth, malnutrition remained a major concern, with millions of infants worldwide affected by underweight, and stunting. Unresolved, this condition led to poor growth, weakened immunity, and delayed cognitive development. Baby-Led Weaning (BLW), a method where infants aged six months and older self-fed solid foods, offered a potential solution by encouraging food exploration, chewing skills, and appetite. Therefore, this study aimed to evaluate the impact of BLW-based complementary feeding on infant weight gain.Methods: This study employed a quasi-experimental design with a one-group pretest-posttest approach. An accidental sampling technique was used to select 15 infants aged 9 to 24 months. The intervention period lasted for 14 consecutive days, during which the BLW method was implemented at the participants' homes under the guidance of the researcher. Data were collected through observations of infant weight measurements and analyzed using a paired t-test. Results: The study found that the average infant weight increased from 9.53 kg before the BLW intervention to 10.05 kg afterward. A paired t-test revealed a statistically significant difference, with a p-value of 0.000 (p < 0.05). Conclusion: These findings indicate that complementary feeding using the BLW method effectively increased infant weight. Therefore, the BLW approach is recommended for mothers introducing complementary foods, as it may support optimal growth and development in infants.